KEEFEKTIFAN PROGRAM INDONESIA PINTAR DI MADRASAH KABUPATEN GORONTALO - Syafrin Ngiode; Alfian Erwinsyah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study aims to determine the effectiveness of the Smart Indonesia Program (PIP) in madrasah, Gorontalo District, Gorontalo Province. This research uses mixed methods. Data collection techniques carried out through observation, interviews, questionnaires, and documentation. The data analysis technique is done in stages, starting from editing, coding tabulating, scoring to drawing conclusions. The results showed that: Input component score is 87 (effective), consisting of guidelines book, objectives, program objectives, PIP recipient requirements, student allocation, fund amount, determination of prospective students receiving assistance, submission of PIP recipients, PIP program funds distribution and withdrawal, realization of PIP disbursement and reporting, are considered effective, because their implementation refers to the technical guidelines for the implementation of the Smart Indonesia Program in madrasah. Output component score of 90 (effective). The indicators on the use of funds are considered effective, because students have used them well to meet their educational needs. The PIP recipient's liability indicator is in the effective category, because in PIP acceptance, madrasah students have an obligation to report the value of their semester results, PIP will be canceled if the requirements are not met.